2020
DOI: 10.1159/000510075
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Multiple Sclerosis Transcriptome Deconvolution Indicates Increased M2 Macrophages in Inactive Lesions

Abstract: Accumulating evidence suggests M2 macrophages contribute to tissue reparation and limit inflammation in multiple sclerosis (MS). However, most studies have focused on murine models without substantial support through human MS observations. The present study aimed to quantify the relative abundances of M2 macrophages in different lesion types excised from human MS patients. CIBERSORTx, an established RNA deconvolution algorithm, was applied on bulk RNA-sequencing data developed from 98 lesions from 10 progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Indeed, the extent of BBB permeability, which disrupts the homeostasis of the CNS immune microenvironment, is directly correlated with disease Li et al J Transl Med (2021) 19:125 severity [1]. According to recent reports in literature, the cells of the immune system such as M1 macrophage/ microglia [2,3], Th1 cell [4,5], Th17 cell [6] play vital roles in exacerbating the MS disease, however, M2 macrophage/microglia [7], Th2 cell [8], regulatory T cell [9] play vital roles in ameliorating the MS disease. Furthermore, many different types of immunocytes such as B cell [10,11], neutrophil [12], dendritic cell [13] and mast cell [14] were involved in the pathogenesis, development or relapse of MS.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the extent of BBB permeability, which disrupts the homeostasis of the CNS immune microenvironment, is directly correlated with disease Li et al J Transl Med (2021) 19:125 severity [1]. According to recent reports in literature, the cells of the immune system such as M1 macrophage/ microglia [2,3], Th1 cell [4,5], Th17 cell [6] play vital roles in exacerbating the MS disease, however, M2 macrophage/microglia [7], Th2 cell [8], regulatory T cell [9] play vital roles in ameliorating the MS disease. Furthermore, many different types of immunocytes such as B cell [10,11], neutrophil [12], dendritic cell [13] and mast cell [14] were involved in the pathogenesis, development or relapse of MS.…”
Section: Introductionmentioning
confidence: 99%
“…The authors searched for the presence of M2 macrophages in white matter using a background dataset of 547 genes for 22 hematopoietic cells. The authors observed a higher abundance of M2 in the lesions of MS during the inactive phase [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a separate PD study making use of RNA-seq datasets from the GEO database, several genes including RPL21 , RPL34 , CKS2 , B2M , TNFRSF10A , DTX2 , and HLA-B , have been shown to be upregulated in PD brain tissues [ 62 ]. In MS, a data mining study analyzing RNA-seq datasets from the GEO database has reported that inactive MS brain lesions contain significantly more M2 macrophages compared to normal white matter controls [ 63 ].…”
Section: Omics Spectrum-based Data Mining In Translational Neurosciencementioning
confidence: 99%